Integration of Fintech, Financial Literacy, and Financial Inclusion with Sustainability Strategy to Support Business Sustainability Micro, Small and Medium Enterprises - Pradnyani, Ni Luh Putu Sri Purnama; Wasita, Putu Aristya Adi; Mendra, Ni Putu Yuria (Indonesian Journal of Sustainability Accounting and Management, 2025)
This research was to analyze the influence of technology and sustainability strategies on the sustainability of Micro, Small, and Medium Enterprises (MSMEs) in Bali. The variables in this research consisted of Business Sustainability that includes growth, strategy, and financial structure; Financial Technology that is measured through usability, ease of use, and risk; Financial Literacy that inclueds financial knowledge, behavior, and attitudes; and Financial Inclusion that includes access, use, and quality of financial services. Furthermore, Sustainable Strategy involves regulatory compliance, economic performance, environmental responsibility, social responsibility, long-term strategic planning, stakeholder engagement. This study used a quantitative method with a survey design with the data, collected through questionnaires distributed to 330 MSME owners. Data analysis was conducted using SmartPLS to explore the relationship between variables and the moderating effect of sustainability strategies. The results of the study showed that financial technology, financial literacy, and financial inclusion had a positive effect on the sustainability of MSME businesses. In addition, sustainability strategies had been shown to strengthen the influence of financial technology, financial literacy, and financial inclusion on business sustainability. These findings provided important insights for stakeholders in formulating policies that support the development of sustainable MSMEs that, not only focus on profitability, but also on social and environmental impacts, in line with the Triple Bottom Line (TBL) principle.